The usage of digital flashcards to teach English vocabulary - Espinoza Guamushi, Nathaly Silvana (2025)
Digital flashcards are an example of a technological tool that has a big impact on education since they assist pupils acquire new vocabulary that is regarded to be relevant to learning English. For this reason, the purpose of this research was to analyze how are the digital flashcards being used to teach English vocabulary to the students of the second year of General Basic Education “A” of the Christian Educational Unit “Nazareno”, city of Riobamba, province of Chimborazo. The dynamic and interactive nature of digital flashcards, which use captivating visual and aural content to teach vocabulary, is making them more and more popular in educational settings. Methodologically, this investigation followed a qualitative approach. The research design project is exploratory, diagnostic level. The population was made up of 30 students of second-year General Basic Education students at Unidad Educativa Cristiana “Nazareno” in Riobamba, Chimborazo province. To obtain the sample, since it is small, it will not need a sample calculation. The techniques used were observation and interview. The instruments used were the Observation Guide and the Interview guide, through which the data were collected and analyzed. The results allowed concluding that digital flashcards are effective in introducing new vocabulary by capturing students’ attention and supporting initial understanding. However, the inconsistent use of contextualized and interactive activities limited the students’ ability to retain and apply the vocabulary in real-life situations. This lack of variety and creative tasks, often due to time constraints, affected students' overall vocabulary competence.